Drivers and motivations of Lebanese women entrepreneurs: insights from the demand-constraint-choice framework - Marcus Goncalves; Nolla Haidar; Elif Celik (Cogent Business & Management, 2024)
This study investigates women entrepreneurs' multifaceted challenges and opportunities in Lebanon, using the Demand-Constraint-Choice (DCC) framework to analyze their drivers, motivations, and challenges. Through a qualitative research approach, the study adopted semi-structured interviews with twelve female entrepreneurs from various sectors in Lebanon. These interviews aimed to gain insights into their entrepreneurial drive, challenges, leadership roles, and decision-making processes within the local entrepreneurial ecosystem. Despite significant socio-economic hurdles, including restricted access to financial resources, prevalent gender biases, and cultural stereotypes, the findings reveal that Lebanese women entrepreneurs are highly resilient and adaptable. They strategically utilize their social networks and innovate within their means to navigate and prosper in the challenging entrepreneurial landscape. The study highlights that these women's entrepreneurial leadership skills include coping with demands and constraints and making difficult choices. The research further identifies critical challenges such as inadequate financial support, societal biases against women, and the difficulties imposed by Lebanon's economic environment. In response to these challenges, the study proposes several policy recommendations to enhance support for women entrepreneurs. These include increasing access to financial resources, establishing robust support networks, and implementing gender-sensitive policies to facilitate a more conducive environment for women's entrepreneurship. It underscores the importance of supporting and empowering women entrepreneurs in Lebanon as vital agents of economic change and innovation, recommending strategic actions to alleviate their challenges and maximize their entrepreneurial potential.
Keywords: 650; Women's entrepreneurship; push-and-pull motivational factors; lebanon; international entrepreneurship; economic development; resilience